KELOMPOK SOSIAL DALAM MASYARAKAT PERSPEKTIF QS. AL-MAIDAH AYAT 2 - Ahmad Zabidi (Borneo : Journal of Islamic Studies, 2020)
Social groups are things that are commonly known in the community both anciently and now. As a result, things like this lead to conflicts in society due to differences in the meaning of social groups themselves, even though in Islamic teachings there are differences in gender, differences in skin color, race, ethnicity, nation and customs which are unique in themselves so that in God's eyes the noble man is human who have a piety and pious personality and are good with fellow humans.